2005
DOI: 10.1128/aem.71.7.4044-4051.2005
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Biofilms to Bdellovibrio bacteriovorus Attack

Abstract: Biofilms are communities of microorganisms attached to a surface, and the growth of these surface attached communities is thought to provide microorganisms with protection against a range of biotic and abiotic agents. The capability of the gram-negative predatory bacterium Bdellovibrio bacteriovorus to control and reduce an existing Escherichia coli biofilm was evaluated in a static assay. A reduction in biofilm biomass was observed as early as 3 h after exposure to the predator, and an 87% reduction in crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
167
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(180 citation statements)
references
References 49 publications
11
167
0
2
Order By: Relevance
“…Strikingly, a different gene-expression profile was obtained in AP cells incubated with prey extract without ghosts: bd0108 and pilA were not silenced, and groES1 and ftsZ, both strongly enhanced in the GP (40,56), were specifically induced. The other GP marker genes (pcnB, dgcB, rpoD, and rpoH) as well as the bdelloplast formation genes (bd0816 and bd3459) and merRNA responded similarly as when incubated with the ghost preparation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strikingly, a different gene-expression profile was obtained in AP cells incubated with prey extract without ghosts: bd0108 and pilA were not silenced, and groES1 and ftsZ, both strongly enhanced in the GP (40,56), were specifically induced. The other GP marker genes (pcnB, dgcB, rpoD, and rpoH) as well as the bdelloplast formation genes (bd0816 and bd3459) and merRNA responded similarly as when incubated with the ghost preparation.…”
Section: Discussionmentioning
confidence: 99%
“…In effect, this scheme represents a prudent betting strategy. In contrast to the successful recognition of the carefully produced prey ghosts, in nature B. bacteriovorus, an effective predator of biofilms (56,60), encounters prey remains from which the first cue is hypothesized to be easily lost, as observed with prey lysate and perforated envelopes (Results).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, previous research showed that the thick polysaccharide capsule is not difficult for Bdellovibrio to penetrate (23), making it easier for B. bacteriovorus to access and efficiently disperse biofilms. It is reported that B. bacteriovorus is able to access biofilms as thick as 30 m (24). To further visualize biofilm predation after treatment with B. bacteriovorus, biofilms predeveloped on coverslips were exposed to B. bacteriovorus or a predator-free control and then analyzed by SEM (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that while B. bacteriovorus can predate an E. coli biofilm, a significant fraction of the biofilm often remains [39], in contrast to predation on planktonic E. coli cultures where only a minute fraction of the population survives due to phenotypic resistance. In the microhabitats under investigation here, part of the prey population grows as a surface-associated biofilm (see electronic supplementary material, movies S1, S4, and S5).…”
Section: Discussionmentioning
confidence: 99%